Composite of bentonite and cyclodextrin as an efficient catalyst for promoting chemical transformations in aqueous media - Fatemeh Koohestani (Nature Portfolio, 2021)
Abstract Combining the encapsulating capability of cyclodextrin and instinctive features of bentonite clay, a versatile metal free catalyst has been developed that could promote various chemical reactions such as Knoevenagel condensation, synthesis of xanthan and octahydroquinazolinones in aqueous media under ultrasonic irradiation. To prepare the catalyst, bentonite was Cl-functionalized and then reacted with isatin and guanidine successively to furnish amino functionalized bentonite. The latter then reacted with tosylated cyclodextrin. The resultant catalytic composite was characterized via XRD, SEM, EDS, BET, elemental mapping analysis, TGA and FTIR. The catalytic activity tests approved excellent activity of the catalyst as well as broad substrate scope. Notably, the catalyst could be simply recovered and reused for several reaction runs. Moreover, the activity of the composite was superior to that of its components.